A Novel α-Globin Chain Variant, Hb Nanchang [HBA2: c.46G>A, Codon 15 (GGT>AGT) (Gly→Ser)], Detected by Matrix-Assisted Laser Desorption Ionization-Time of Flight Mass Spectrometry. (4th July 2021) - Xu, Anping; Chen, Weidong; Xie, Weijie; Zheng, Huiqi; Zhou, Yu; Ji, Ling
Abstract: Here we report a new α chain variant accidentally discovered during Hb A1c measurement by matrix-assisted laser desorption ionization-time of flight (MALDI-TOF) mass spectrometry (MS) that revealed the presence of a variant α chain with a mass of 15155 Da. However, this hemoglobin (Hb) variant cannot be detected by the first-line methods such as cation exchange high performance liquid chromatography (HPLC) and capillary electrophoresis (CE). Sanger sequencing confirmed the presence of a heterozygous missense mutation [ HBA2 : c.46G>A, codon 15 ( G GT> A GT), (Gly→Ser)]. The theoretical mass difference (30 Da) due to the substitution of amino acid glycine to serine matched the actual measured mass difference (29 Da). As this is the first report of the mutation, we named it Hb Nanchang after the place of residence of the proband.